A new iridoid, verbascoside and derivatives with inhibitory activity against Taq DNA polymerase - Garro, Hugo Alejandro (2015)
DNA polymerases are enzymes that play a crucial role in DNA metabolism such as replication, repair, transcription, recombination, and chromosome segregation during mitosis. Herein we report the isolation of a new iridoid (6-epi-catalpol, 2) and per-O-acetyl-verbascoside (11) from aerial part of Buddleja cordobensis Grisebach (Buddlejaceae). From compound 2, we have obtained eight compounds by chemical transformation. This group of compounds at a concentration of 500 μM was assayed against Taq DNA polymerase. Compound 11 (per-O-acetyl-verbascoside) was the most active with an IC50 of 1.21 + 0.18 μM; compounds 9, 2 and 8 were strong inhibitors with IC50 values of 5.57 + 0.70, 21.62 + 0.22 and 78.13 + 0.93 μM, respectively. Compounds 11 and 9 could be a leader structures to development new anticancer chemotherapy medicines and a useful tool to investigate DNA polymerase activity.